Development of Sustainable Bioplastic Composite Films from Cocoa Pod Husk Waste Cellulose and Kappa-Carrageenan - Esa Ghanim Fadhallah; Ahmad Sapta Zuidar; Sri Hidayati; Haidawati Haidawati; Amarilia Harsanti Dameswary; Aisyah Tri Ramadhani (Caraka Tani: Journal of Sustainable Agriculture)
Cocoa pod husk (CPH), typically considered agricultural waste, contains cellulose suitable for bioplastic production, offering a sustainable alternative to synthetic plastics. Its reinforcement with kappa-carrageenan is designed to improve the properties of cellulose-based bioplastics while reducing agricultural waste. This study evaluates the effects of cellulose from CPH waste and kappa-carrageenan formulations on bioplastic properties. The cellulose was isolated through a delignification and bleaching process, while the bioplastics were prepared by varying the ratios of cellulose and kappa-carrageenan in six different formulations. The resulting films were evaluated for their physical, mechanical, and barrier properties, as well as their stability and biodegradability. The ratio of cellulose to kappa-carrageenan significantly impacts the films’ properties. Significant improvements in tensile strength were observed in P5 (2 g cellulose, 8 g kappa-carrageenan) and P6 (10 g kappa-carrageenan), increasing by 79% and 240%, respectively, as the cellulose concentration decreased and kappa-carrageenan increased. However, the significant drawback in barrier properties was found in water vapor transmission rate (WVTR), with the higher kappa-carrageenan and lower cellulose concentrations films resulting in increased WVTR values by 13% (P5) and 17% (P6). The bioplastic with P1 (8 g cellulose, 2 g carrageenan), P2 (6 g cellulose, 4 g carrageenan), P3 (5 g cellulose, 5 g carrageenan), and P4 (4 g cellulose, 6 g carrageenan) formulations completely degraded in 3 weeks, while those with higher kappa-carrageenan content degraded faster, with P5 completely degrading in 2 weeks and P6 in 1 week. This study implies a potential reduction in environmental impact by replacing conventional plastics with the development of biodegradable materials derived from agricultural waste and promoting sustainable agricultural practices by utilizing CPH.